2006
DOI: 10.1038/sj.jhh.1002025
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive antihypertensive strategies based on hydrochlorothiazide, candesartan or lisinopril decrease left ventricular mass and improve arterial compliance in patients with type II diabetes mellitus and hypertension

Abstract: We investigated the effects of aggressive antihypertensive therapy based on hydrochlorothiazide, candesartan or lisinopril on left ventricular mass (LVM) index and arterial stiffness in hypertensive type II diabetic individuals. Seventy hypertensive type II diabetic individuals were treated with three antihypertensive strategies in a randomized, double-blind, double-dummy design. Blood pressure was titrated to levels below 130/ 85 mm Hg or a decrease in systolic pressure of 10% with a diastolic pressure below … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 47 publications
1
10
1
1
Order By: Relevance
“…24,25 In the present study, age, baseline SBP and pulse pressure were positively correlated to the effects of SBP reduction by thiazide treatment, suggesting the possible early presence of increased stiffness of large arteries even in a cohort of mainly middle-aged hypertensives. 26,27 Accordingly, thiazide diuretics either alone or in combination may have particular beneficial effects not only on elderly patients 28,29 but also on younger patients with increased arterial or aortic stiffness as that shown in the present study.…”
Section: Identification Of the Thiazide Responders C-c Huang Et Almentioning
confidence: 50%
“…24,25 In the present study, age, baseline SBP and pulse pressure were positively correlated to the effects of SBP reduction by thiazide treatment, suggesting the possible early presence of increased stiffness of large arteries even in a cohort of mainly middle-aged hypertensives. 26,27 Accordingly, thiazide diuretics either alone or in combination may have particular beneficial effects not only on elderly patients 28,29 but also on younger patients with increased arterial or aortic stiffness as that shown in the present study.…”
Section: Identification Of the Thiazide Responders C-c Huang Et Almentioning
confidence: 50%
“…14,22,25,27,28,41,69,78,79,84,88,89,92 Apart from one study in which there was a greater reduction of left ventricular hypertrophy with an ARB, 89 there were no differences between ACE inhibitor and ARB groups. Only one study evaluated a DRI; it found similar effects between aliskiren and an ARB.…”
Section: Left Ventricular Mass or Functionmentioning
confidence: 99%
“…12 These findings in relation to the thiazide diuretics and the angiotensin II blockers are novel. [13][14][15] Thiazide diuretics have different pharmacologic properties that may affect arterial aging. Indeed, the increase in arterial stiffness with thiazide use might be linked by the calcium metabolism.…”
mentioning
confidence: 99%
“…[15][16][17][18][19][20][21] Although pathophysiologically very important, arterial stiffness is still a surrogate end point and what finally counts for the clinician (and for the patient) is the effect of treatment on cardiovascular morbidity and mortality (as proven in large randomized controlled trials). Therefore, there is still a need for data from prospective short term and long-term studies assessing the effects of the so-called 'cardiovascular protective drugs' on arterial aging and on clinical outcome data, thereby comparing results on the basis of central hemodynamic parameters with results based on peripheral measures.…”
mentioning
confidence: 99%